Induction of CD14 Expression and Differentiation to Monocytes or Mature Macrophages in Promyelocytic Cell Lines: New Approach - Fatemeh Zamani; Fatemeh Zare Shahneh; Leili Aghebati-Maleki; Behzad Baradaran (Tabriz University of Medical Sciences, 2013)
Purpose: CD14, one of the main differentiation markers on the surface of myeloid lineage cells, acts as a key role in activation of LPS-induced monocytes. LPS (lipopolysaccharide) binds to LPS-binding protein in plasma and are delivered to the cell surface receptor CD14. In this study, Various stimuli [Dimethyl Sulfoxide (DMSO), active 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] and LPS], either alone or in combination, have been recognized that have an effect on the level of CD14 expression in the human HL-60 and U937 promonocytic cell lines and therefore induce their terminal differentiation into monocytes or mature macrophages. Methods: U937 and HL-60 cells were cultured in RPMI 1640 supplemented with 10% FBS. For each cell line, 1×106 cells were seeded for 72 hours with DMSO, 14 days with LPS and 18 days with 1, 25-D3 in each well plate; then ELISA method was used to study their responses to the factors by means of anti-CD14. Results: ELISA assay demonstrated that U937 and HL-60 cells were induced by both [1,25(OH)2D3] and DMSO to obtain characteristics of adherent cells and express CD14 protein; moreover, LPS at a low dose increased CD14 expression on surface of this cells. Conclusion: According to the our results, it is speculated that CD14 gene expression may be induced in human U937 and HL-60 cell lines by different factors including 1,25-D3, DMSO and LPS.